(untitled) (Zoological Records and Reviews, 2023)
Pollinators – primarily wild bees, hoverflies, butterflies, moths, and beetles – provide essential ecosystem services that underpin both the reproductive success of wild plant communities and the productivity of agricultural systems, while themselves depending on the floral diversity, nesting resources, and landscape connectivity that biodiversity conservation maintains. This mutualistic interdependence makes pollinators both ecological cornerstones and sensitive indicators of ecosystem health. This review synthesises evidence from 204 primary studies (2005-2023) examining the ecological roles of pollinators in European biodiversity conservation, evaluating four interconnected dimensions: pollinator contributions to wild plant reproductive success and community assembly, pollinator population trends and drivers of decline, pollinator-plant network structure and robustness, and conservation management approaches for pollinator-inclusive landscape management. Wild bees provide pollination services to 84% of European flowering plant species and are implicated in the reproductive success of 78% of European crop species. European wild bee diversity has declined by an estimated 37% over 1980-2020 based on Red List assessments, with agricultural intensification (pesticides, habitat loss, floral resource reduction) as the primary driver in 82% of assessed declining species. Pollinator-plant interaction networks show functional redundancy in most European systems but are vulnerable to the loss of specialist interaction links in simplified agricultural landscapes. Habitat management interventions – agri-environment wildflower strips, hedgerow restoration, reduced mowing frequency – increase pollinator abundance by 48-148% in paired comparison studies. Implications for the EU Pollinators Initiative, Common Agricultural Policy agri-environment scheme design, and Nature Restoration Law agricultural ecosystem restoration targets are discussed.